Cold atmospheric plasma therapy in wound healing. (January 2022) - Dubey, Sunil Kumar; Parab, Shraddha; Alexander, Amit; Agrawal, Mukta; Achalla, Vaishnav Pavan Kumar; Pal, Udit Narayan; Pandey, Murali Monohar; Kesharwani, Prashant
Graphical abstract: Highlights: Cold atmospheric plasma improves cell proliferation. Cold atmospheric plasma improves synthesis of Extracellular matrix protein. Cold atmospheric plasma promotes vascularization at wound site. Cold atmospheric plasma improved microcirculation. Cold atmospheric plasma restricts the spread of infectious microorganism. Abstract: Cold atmospheric plasma therapy is a new and latest approach whose arrival has astonished experts all around the world from the area of biological and pharmaceutical sciences. Owing to its simple and non-invasive nature, this technique has been admired and encouraged to use different therapeutic regimes like wound healing, ulceration, and cancer. It is often confused with blood plasma but is identified as the fourth state of matter generated using feed gases like atmospheric air, argon, helium either by applying irradiation or electric field. The non-thermal property of plasma (cold plasma) is mainly focused on the clinical application as it utilizes lower temperatures (<40 °C) and compatible for biomedical applications. The present review emphasizes the application of cold atmospheric plasma in wound healing. The work briefly discusses the types of wounds, the process of wound healing, existing techniques of wound healing followed by the role of cold atmospheric plasma therapy in wound healing. In cold plasma therapy, we have highlighted the methods of generating cold plasma beam for application on the wound, mechanism of healing by cold atmospheric plasma and some of the recent studies reported the use of cold plasma in wound healing.